Integrated modelling of the Globus-M tokamak plasma and a comparison with SOL width scaling. (15th April 2015) - Senichenkov, I.Yu.; Kaveeva, E.G.; Gogoleva, A.V.; Vekshina, E.O.; Zadvitskiy, G.V.; Molchanov, P.A.; Rozhansky, V.A.; Voskoboynikov, S.P.; Khromov, N.A.; Lepikhov, S.A.; Gusev, V.K.
Abstract: Recently a scheme for the coupling of the one-dimensional core transport code ASTRA and the two-dimensional edge transport code B2SOLPS was developed, thus providing the integrated modelling of tokamak discharge. Here, this scheme is improved by taking impurities into account and by considering a real flux surface shape using the equilibrium code SPIDER. This integrated modelling is applied to discharges of the spherical tokamak Globus-M to study the dependence of the scrape-off layer (SOL) width and divertor heat loads on the discharge power and the plasma current. Since these values, together with the magnetic field, are relatively small in Globus-M, this study can test the existing scaling against data in a wider range of tokamak operational parameters. The modelling results agree reasonably with Thomson scattering and Langmuir probe measurements and allow, in principle, the determination of the physical mechanisms responsible for the SOL structure formation. It is found that the SOL width is approximately inversely proportional to the plasma current, in agreement with existing experimental scaling, while its dependence on discharge power is found to be quite weak.